THE RIGHTS OF PEOPLE WITH DISABILITIES "A MIRROR WHERE TO LOOK AT YOURSELF, IN THE SPANISH DIGITAL PRESS" - Vidal-García, Josefa (2021)
ABSTRACT People with disabilities are part of vulnerable minorities, on them and their image, the use of obsolete terminology in the current media falls. The objective of this research it was to analyse the social representations of people with disabilities in the Spanish media, as a constitutive factor of social reality, social representation. It was examined, quantified, analysed, and interpreted, how people with disabilities are represented in a recent period, through a retrospective content investigation, which allows us to visualize and quantify that reality, facilitating actions focused on promoting equality, that which should always prevail in a just and equitable society. The data collection for the study was both qualitative and quantitative through selected articles for 36 months (2017-2019), from four Spanish presses. 677 articles related to disability were obtained. It is concluded that the Spanish digital presses continue anchored in the past, stereotypes continue to surround journalism professionals regarding these groups; In addition, there are differences between the different selected presses, although there is still much work to be done and the specialized training of journalism professionals depends on it to begin to make these groups of people visible from the schools. Keywords: quality of life - inclusion-media - people with disabilities - digital press -social representations